2021
DOI: 10.1038/s41598-020-79264-4
|View full text |Cite
|
Sign up to set email alerts
|

Adults with current asthma but not former asthma have higher all-cause and cardiovascular mortality: a population-based prospective cohort study

Abstract: Higher mortality in asthmatics has been shown previously. However, evidence on different asthma phenotypes on long-term mortality risk is limited. The aim was to evaluate the impact of asthma phenotypes on mortality in general population. Data from the National Health and Nutrition Examination Survey from 2001–2002 to 2013–2014 linked mortality files through December 31, 2015, were used (N = 37,015). Cox proportional hazards regression was used to estimate the risk of all-cause and cause-specific mortality adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Second, the inclusion criteria for asthma patients were one hospitalization, two outpatient visits, or two emergency department visits for asthma within 12 months, whereas most of the other studies based the inclusion criteria on questionnaires about self-reported asthma history. Thus, all of the asthma patients in that study had active and more severe asthma and, therefore, higher CVD morbidity and mortality risk than non-active asthma patients ( 37 , 40 ).…”
Section: Discussionmentioning
confidence: 79%
“…Second, the inclusion criteria for asthma patients were one hospitalization, two outpatient visits, or two emergency department visits for asthma within 12 months, whereas most of the other studies based the inclusion criteria on questionnaires about self-reported asthma history. Thus, all of the asthma patients in that study had active and more severe asthma and, therefore, higher CVD morbidity and mortality risk than non-active asthma patients ( 37 , 40 ).…”
Section: Discussionmentioning
confidence: 79%
“…However, the evidence for ED in asthma is not as great as that in COPD [ 7 ]. ED is typically present in asthmatic adults [ 26 ]. Reduced flow-mediated dilatation (FMD) levels in asthmatics—a relation of FMD to asthma severity confirming a worsening endothelial function with disease progression—are also found in patients with COPD [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…After applying the inclusion and exclusion criteria, we included 18 observational studies (9, 14-30) (Figure 1). Among these, 2 studies (21,22) were identified in the manual search and 16 studies (9,(14)(15)(16)(17)(18)(19)(20)(23)(24)(25)(26)(27)(28)(29)(30) were identified in the electronic search.…”
Section: Resultsmentioning
confidence: 99%
“…Among 18 the observational studies included, 10 were crosssectional studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Of these, 2 were cohort studies (21,28) that did not have outcomes of interest, but reported crosssectional data on the association between asthma and stroke in the baseline characteristics of the population. The other 8 cross-sectional cohort studies (9, 14-20) included 2 retrospective studies (17,19) and 6 prospective studies (9, 14-16, 18, 20).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation